Engaging in the prevention of pressure injuries in spinal cord injury: A qualitative study of community-dwelling individuals' different styles of prevention in Switzerland. (3rd March 2020) - Zanini, Claudia; Brach, Mirjam; Lustenberger, Nadia; Scheel-Sailer, Anke; Koch, Hans Georg; Stucki, Gerold; Rubinelli, Sara
Abstract : Context: Spinal cord injury (SCI) is a complex chronic condition with multiple self-management requirements and a high prevalence of complications. Pressure injuries (PIs) are among the most common ones and represent a frequent reason for re-hospitalization. This study aimed to identify styles of prevention that individuals with SCI adopt to deal with the risk of developing PIs. Design: Qualitative explorative interview study. Data was collected through semi-structured interviews, which were transcribed verbatim and analyzed following the principles of thematic analysis. Setting: Switzerland. Participants: The participants were a purposive sample of community-dwelling Swiss residents with SCI for at least five years. Interventions: Not applicable. Outcome measures: Not applicable. Results: Although all participants (N = 20) showed at least a basic knowledge of prevention of PIs by describing some preventive measures, they had different prevention styles characterized by different behavioral patterns (i.e. complying with all recommended measures, performing only a selection of them or delegating them to others) and different beliefs and attitudes towards prevention. Conclusion: By identifying the style of prevention of an individual, it is possible to develop tailored interventions that have an impact on the factors which seem to play a role in determining the adoption of preventive behaviors (i.e. perceived susceptibility to PIs, attitudes towards prevention, and self-efficacy). Such interventions would constitute a concrete effort to support individuals with SCI during their self-management. Besides alleviating a frequent and disabling medical complication and contributing to an enhanced quality of life, these interventions might also help decrease healthcare costs.